fructificación del hongo ECM comestible Amanita ponderosa Malençon & R. Heim durante seis años consecutivos en un encinar adehesado de la Sierra (Investigación Agraria: Sistemas y Recursos Forestales, 2007)
Number and location of Amanita ponderosa Malençon & R. Heim sporocarps was followed through six years in a 3 ha holm-oak forest located in the Sierra de Aracena y Picos de Aroche Natural Park (Huelva), at the Southwest of Spain. The data indicated that patches of sporocarp production showed a very similar shape each year, but some spots showed differences seeming crop alternance or mast years. This species only fructifies in spring, being the fruiting period from 6 to 8 weeks, what coincides with the increasing of air-temperature from mid February to April. Differences in fruiting period length and total sporocarp production are related to rainfall and temperature. Results suggest that rainfalls at the end of summer and early autumn are crucial for the next spring fruiting, but rainfalls during fruiting period seem to have less influence in sporocarp production. During the sporocarp production period, it was related to soil temperature.